2020
DOI: 10.3390/ijms21228475
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 Efficacy Test for Human Skin Equivalents Using a Pumpless Skin-On-A-Chip System

Abstract: A human skin equivalent (HSE) composed of the epidermis and dermis is cultured using a pumpless skin-on-a-chip system to supply cultures the desired flow rate using gravity flow without a pump or an external tube connection. Coenzyme Q10 efficacy is tested by adjusting its concentration, as it is known to have anti-aging and antioxidant effects in culture solutions. The relationship between the contraction rate of a full-thickness human skin equivalent and secreted transforming growth factor (TGF) β-1 is analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Three type I collagen studies have confirmed that rat-tail collagen is the most appropriate scaffold [ 32 ] and that pumpless SOC produces anticancer-drug-induced side effects on the skin [ 33 ] and anti-aging effects. We have reported the effects of curcuma longa leaf extract (CLLE) [ 34 ] and CoQ10 drugs [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Three type I collagen studies have confirmed that rat-tail collagen is the most appropriate scaffold [ 32 ] and that pumpless SOC produces anticancer-drug-induced side effects on the skin [ 33 ] and anti-aging effects. We have reported the effects of curcuma longa leaf extract (CLLE) [ 34 ] and CoQ10 drugs [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the skin is damaged, it activates cytokines’ expression, causing inflammation in the damaged area and fighting against the potential intruder pathogens. Angiogenesis and the pro-angiogenic factors like PDGF (platelet-derived growth factor), VEGF (vascular endothelial growth factor), and TGF-β (transforming growth factor β) can help in the regeneration of the tissue by stimulating the proliferation, migration, and tube formation of endothelial cells [ 87 , 88 , 89 , 90 ]. Studies have shown similarities in the skin defense reaction and repairing mechanism in high UV exposure and skin surface damage, including inflammation, increased cell migration, and proliferation [ 83 , 91 ].…”
Section: Utilization Of Skin-on-a-chip Systemsmentioning
confidence: 99%
“…As different warning signs appear in a tissue, cytokine expression and release increases for activating the defense of the body. This signal cascade can be started by tissue damage, pathogens, and foreign bodies, but in the case of the skin, it can also be the consequence of high exposure to UV light [ 83 , 88 , 89 , 90 ].…”
Section: Utilization Of Skin-on-a-chip Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research confirmed that providing media to a pumpless skin-on-a-chip system with gravity flow using 3D skin equivalents cultured on transwell inserts and microfluidic chips provided sufficient nutrients for cells to multiply and differentiate [ 24 ]. Furthermore, human skin equivalent models that use pumpless skin-on-a-chip systems with gravity flow are used as part of drug screening platforms to evaluate drug efficacy [ 24 , 30 , 31 , 32 , 33 , 34 ]. A previous study also confirmed that the thickness of the epidermal layer was increased by mechanical stretching [ 35 ].…”
Section: Introductionmentioning
confidence: 99%